Stand-up Comedy, Perbedaan Etnis, dan Konflik Kajian Teoritis Komunikasi Lintas Budaya - Are Embu Hendriquez (Atma Jaya Indonesia Catholic University, Jakarta, 2012)
A chaotic tragedic riots happened in May 1998 where the majority of the victims were Chinese ethnics as a sign that stereotypes, prejudices, hates between Chinese ethnics group and non- Chinese werestill going on in Indonesia. Meanwhile, the new recent Chinese generation, however is different from his/her anchestors. Therefore intercultural communication is needed to close the gap. One of thecommunication forms that would be able to reduce stereotypes, prejudices, and hates is standup comedy. This article looks at how mindfulness can be done through a non-serious dialogue to create common understanding.